Mechanical Ventilation in Neonatal Respiratory Distress Syndrome at High Altitude: A Retrospective Study From Tibet - Chen, Dan; Liu, Xiuxiu; Li, Jiujun (Frontiers in Pediatrics, 2019)
Objective: To explore the characteristics of mechanical ventilation parameters and the arterial partial pressure of oxygen in neonatal respiratory distress syndrome (RDS) at high altitude. Methods: From the 1st May 2017 to the 31st December 2018, we recruited 33 neonates with severe RDS who were undergoing mechanical ventilation in the NICU of Naqu People's Hospital in Tibet (4580 m above sea level); these neonates formed a plateau observation group. We also recruited a non-plateau control group: 66 neonates with severe RDS undergoing mechanical ventilation of Shengjing Hospital in Liaoning (51 m above sea level). Various ventilation parameters and the arterial partial pressure of oxygen were then compared between the two groups, between the survivors of the two groups, and between those who died and survived in the plateau group. Results: In terms of initial ventilator parameters, peak inspiratory pressure (PIP), positive end expiratory pressure (PEEP), and the fraction of inspired oxygen (FiO2) in the plateau group were significantly higher than those in the non-plateau group (P < 0.01). PIP, PEEP, and FiO2 in the survivors from the plateau group were also significantly higher than those in the non-plateau group (P < 0.01). In addition, the arterial partial pressure of oxygen in the non-plateau group was higher (P < 0.05) than that in the plateau group during the early postnatal period, and the arterial partial pressure of oxygen at 6 h and 12 h was lower than that in the plateau group (P < 0.05). Conclusion: Mechanical ventilation can effectively improve the arterial oxygen partial pressure and reduce the mortality of newborns with RDS in a plateau environment. It was clearly evident that ventilation parameters are closely related to altitude. It is therefore not advisable to apply mechanical ventilation parameters used in a non-plateau area as a guide for the treatment of newborns with RDS in plateau areas.